CeO2 pellet fabrication as spent fuel matrix analogue. Issue 14 (November 2016) - Fernandez, S.; Nieto, M.I.; Cobos, J.; Moreno, R.
Abstract: The near field performance assessment of the final high level waste disposal requires information about the spent fuel matrix dissolution because it constitutes the largest source of radionuclides under repository conditions. A possible way to single out the effects of matrix corrosion behaviour of irradiated fuel is to study CeO2 as an inactive analogue of the irradiated UO2 matrix. The aim of this work was the production and characterization of CeO2 pellets with the same microstructure as that obtained for irradiated matrix for further simulation studies. Radial pellets with two zones were fabricated by a two-step process in which the inner ring was obtained by axial pressing and the outer ring by slip casting using well-dispersed, concentrated aqueous suspensions. Porous samples were also obtained by colloidal routes using fructose as pore former. Green samples were sintered at 1600 °C in air and characterised by XRD and SEM.